Acidic microenvironment enhances MT1-MMP-mediated cancer cell motility through integrin β1/cofilin/F-actin axis. (27th September 2021) - Liang, Lubiao; Sui, Ran; Song, Yongxiang; Zhao, Yajin
Abstract: Tumor acidic microenvironment is the main feature of many solid tumors. As a part of the tumor microenvironment, it has a profound impact on the occurrence and development of tumors. However, the research on how tumor cells sense the changes of the external microenvironment and how the intracellular subcellular structures transmit the signals from extracellular to intracellular is unclear. In this study, we identify that the acidic microenvironment enhances cancer cell motility, and the expression of membrane-anchored membrane type 1-matrix metalloproteinase is also associated with cell motility, which indicates more degradation of the ECM under the acidic microenvironment. Moreover, the expression of cofilin is low in the acidic microenvironment, and the F-actin filaments are distributed more along the cells. The cytoskeletal F-actin changes are consistent with the potential of a high-invasive phenotype. Further study reveals the upstream control of the signal transductions from extracellular to intracellular, that is, the integrin β1 functions to trigger the biological responses under the acidic microenvironment. Our results demonstrate that the acidic microenvironment enhances cancer cell motility through the integrin β1/cofilin/F-actin signal axis. This study clearly shows the scheme of the signal transmissions from extracellular to intracellular and further reveals the cytoskeletal roles for the contributions of cancer cell motility under acidic microenvironment, which provides new targets for cancer intervention from the biochemical and biophysical perspectives.